Holistic synthesis of iron-based metal-organic frameworks using unconventional metal feedstock and polyethylene terephthalate derived organic linkers - Musyoka, Nicholas M. (University of Pretoria, 2023)
Dissertation (MSc (Chemistry))--University of Pretoria, 2022.